The Lipoprotein Transport System in the Pathogenesis of Multiple Myeloma: Advances and Challenges - Lazaris, Vasileios; Hatziri, Aikaterini; Symeonidis, Argiris; Kypreos, Kyriakos E. (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is an incurable neoplastic hematologic disorder characterized by malignant plasma cells, mainly in the bone marrow. MM is associated with multiple factors, such as lipid metabolism, obesity, and age-associated disease development. Although, the precise pathogenetic mechanisms remain unknown, abnormal lipid and lipoprotein levels have been reported in patients with MM. Interestingly, patients with higher APOA1 levels, the major apolipoprotein of high density lipoprotein (HDL), have better overall survival. The limited existing studies regarding serum lipoproteins in MM are inconclusive, and often contradictory. Nevertheless, it appears that deregulation of the lipoprotein transport system may facilitate the development of the disease. Here, we provide a critical review of the literature on the role of lipids and lipoproteins in MM pathophysiology. We also propose novel mechanisms, linking the development and progression of MM to the metabolism of blood lipoproteins. We anticipate that proteomic and lipidomic analyses of serum lipoproteins along with analyses of their functionality may improve our understanding and shed light on novel mechanistic aspects of MM pathophysiology.